Diagnosis of left ventricular functional status on physical and mechanical characteristics of myocardial - Чибісов [Viktor Chibisov] Віктор Іванович; Говоруха [Alena Govorukha] Олена Олексіївна; Ніколаєв [Nickolai Nikolaev] Микола Іванович; Рейдерман [George Reyderman] Юрій Ізраилевич; Сухомлин [Vladimir Sukhomlin] Володимир Іванович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> This article contains information about how to use for diagnosis of functional State of the cardiovascular system in addition to traditional of hemodynamics (percussion and minute volume, ejection fraction) and indicators of physical and mechanical properties of gradient-elastic modulus and stress strain State of myocardial wall. The authors developed a methodology for calculating these indicators according to the measurement of echocardiography. The use of these indicators will enhance the expensive equipment for ultrasonic examination of cardio vascular diseases and improve the quality of diagnosis. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>